12 years of "INSPEDUC", the mailing list of school inspectors - Faci Lucia, Fernando (Avances en Supervisión Educativa, 2014)
A review of the twelve years of the use and operation of the mailing list inspeduc@egrupos.net where there are currently over 750 subscribed email addresses of educational inspectors (the vast majority) and other professionals or researchers performed Spain and Latin America. Other possibilities for information dissemination, communication between professionals and creating shared knowledge are assessed.